Analysis of metabolites change from reflorescence buds of ‘Cuiguan’ pear (Pyrus pyrifolia) based on LC-MS/MS - Zhong, Bifeng; Jiang, Linjia; Tian, Yun; Li, Wengui; Zhong, Min; Zhang, Quanjun (Frontiers in Plant Science, 2025)
Developed buds of pears (Pyrus pyrifolia) remain in a dormant state and do not break dormancy until the following spring. However, climatic factors and leaf diseases trigger defoliation in late summer and early autumn, which typically results in the bud paradormancy release and subsequent sprouting. This not only depletes tree nutrients but also diminishes the quantity of flowers and the yield of fruit in the following summer. In this study, metabolic changes in ‘Cuiguan’ pear buds were investigated following premature leaf fall. A total of 1,533 metabolites were annotated, with the majority being downregulated. Sugar levels decreased during the release of paradormancy, likely to provide energy for subsequent growth. Concurrently, most amino acids were consumed post-defoliation, with only a few showing increased trends. Furthermore, the observed low levels of phenylpropanoid-related metabolites in flower buds may contribute to premature senescence. This metabolic profile contributes to our understanding of the biological mechanism of paradormancy release from defoliation, and clarifies the metabolic changes during this process.